Global health diplomacy in nursing, reinforcing challenges and benefits: A scoping review - Arthur Luiz Barbosa Martins; Patrícia de Paula Queiroz Bonato; Bruna Sordi Carrara; Emerson Lucas Junio Silva Lucas Silva Camargo; Carla Aparecida Arena Ventura (Nursing Practice Today)
Background & Aim: Global health diplomacy has become increasingly relevant in nursing, enabling nurses to address complex international health challenges. This literature review examines the challenges and benefits of nurses’ involvement in global health diplomacy, focusing on their unique contributions to international healthcare. Methods & Materials: A scoping review was conducted in November 2024 using databases including PubMed, Scopus, Web of Science, CINAHL, and LILACS. Two independent researchers selected and analyzed studies, consolidating existing literature on nursing and global health diplomacy. The review highlights the field's complexities, opportunities, and nurses’ roles in advancing global health. Results: From 9 selected articles, findings were categorized into three themes: 1) integrating nursing education with global health, 2) professional skill enhancement and engagement in diplomacy, and 3) ethical practices and cultural sensitivity. Nurses face challenges such as navigating complex healthcare systems, cultural differences, and language barriers. However, their contributions significantly influence global health policies, improve healthcare access in underserved regions, and advocate for vulnerable populations. Engaging in global health diplomacy expands nurses’ professional scope, enriches cultural understanding, and fosters leadership development. Limitations include the qualitative nature of available data and the evolving dynamics of global health diplomacy. Conclusion: Nurses involved in global health diplomacy play a pivotal role in strengthening healthcare systems and advancing health equity. Despite existing challenges, their contributions yield substantial benefits. Future research should explore the impact of global health diplomacy on nursing practices, considering healthcare systems' contextual and local nuances.